1989
DOI: 10.1128/mcb.9.3.1365
|View full text |Cite
|
Sign up to set email alerts
|

Conserved sequence blocks in kinetoplast minicircles from diverse species of trypanosomes.

Abstract: Kinetoplast DNA minicircles from various species of trypanosomes are heterogeneous in nucleotide sequence to various degrees but in all instances contain a conserved sequence region of 100 to 200 base pairs present in one, two, or four copies per minicircle. Comparison of the conserved sequence regions of minicircies from eight species of trypanosomes revealed a common sequence motif consisting of three conserved sequence blocks (CSBs) present in the same order and with similar spacing in all species. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 30 publications
2
76
0
4
Order By: Relevance
“…Previous electron microscopic (EM) and gel electrophoresis analyses of B. saltans DNA had revealed the presence of large numbers of minicircle-like DNAs of approximately 1+4 kb (Blom et al+, 1998a)+ To further assess their identity, we cloned and sequenced a number of these molecules in procedures involving digestion of total DNA with either EcoRI or HindIII and ligation of the gel-excised linearized 1+4-kb DNAs into a cloning vector+ From each procedure, two 1+4-kb inserts were sequenced+ Comparison of their nucleotide sequences (Fig+ 1A) showed that they contained regions of almost complete identity (nt 800-1150) interspersed with stretches of a more variable sequence, resulting in an overall identity of 63-74%+ The conserved region proved to contain a sequence (GGGGTTGATATA) with 10 out of 12 matches to CSB-3 (GGGGTTGGTGTA), a conserved dodecamer motif present in all trypanosomatid minicircles, which is possibly involved in replication (Birkenmeyer et al+, 1987;Ray, 1989)+ Adjacent to the conserved region, the sequences contained phased homopolymeric dA•dT tracts, similar to those found in trypanosomatid minicircles, in which they cause bending of the DNA and anomalous migration on polyacrylamide gels (Ntambi et al+, 1984;Ray et al+, 1986)+ Next, we screened the sequences for the presence of gRNA genes, by looking for complementarity to the available edited mRNA sequences from B. saltans (Blom et al+, 1998a) and other kinetoplastids+ Indeed, we found two areas in pBMH06 and pBMH07 with the potential to form a perfect duplex of 46 and 49 nt, respectively, with parts of edited B. saltans ND5 mRNA, if G:U basepairing is allowed (Fig+ 1B)+ Primer extension analysis with total B. saltans RNA and oligonucleotides complementary to the 39 part of the encoded (putative) gRNAs, further showed the existence of RNAs with 59 ends at the positions expected (Fig+ 1B)+ From this, we concluded that these two 1+4-kb DNAs each contain a gRNA gene, completing their identification as the B. saltans equivalent of minicircles+ The two ND5 gRNA genes were of opposite polarity and located in different regions that lack any obvious sequence identity to the corresponding regions of other B. saltans minicircles+ Sections of other minicircles that aligned with these two gRNA genes (Fig+ 1A) appeared to be the only two locations that harbor gRNA genes (see below) and they are referred to as gRNA gene cassettes I and II (see Fig+ 1A,C)+ Both cassettes are preceded by a conserved 35-nt sequence element (inverted repeat, see Fig+ 1A) and are flanked by stretches of 8-10 C residues, although the location of the C-stretch downstream of cassette I varied between minicircles+ A map describing the features of a typical B. saltans minicircle is presented in Figure 1C+ …”
Section: Cloning and Sequencing Of B Saltans Minicirclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous electron microscopic (EM) and gel electrophoresis analyses of B. saltans DNA had revealed the presence of large numbers of minicircle-like DNAs of approximately 1+4 kb (Blom et al+, 1998a)+ To further assess their identity, we cloned and sequenced a number of these molecules in procedures involving digestion of total DNA with either EcoRI or HindIII and ligation of the gel-excised linearized 1+4-kb DNAs into a cloning vector+ From each procedure, two 1+4-kb inserts were sequenced+ Comparison of their nucleotide sequences (Fig+ 1A) showed that they contained regions of almost complete identity (nt 800-1150) interspersed with stretches of a more variable sequence, resulting in an overall identity of 63-74%+ The conserved region proved to contain a sequence (GGGGTTGATATA) with 10 out of 12 matches to CSB-3 (GGGGTTGGTGTA), a conserved dodecamer motif present in all trypanosomatid minicircles, which is possibly involved in replication (Birkenmeyer et al+, 1987;Ray, 1989)+ Adjacent to the conserved region, the sequences contained phased homopolymeric dA•dT tracts, similar to those found in trypanosomatid minicircles, in which they cause bending of the DNA and anomalous migration on polyacrylamide gels (Ntambi et al+, 1984;Ray et al+, 1986)+ Next, we screened the sequences for the presence of gRNA genes, by looking for complementarity to the available edited mRNA sequences from B. saltans (Blom et al+, 1998a) and other kinetoplastids+ Indeed, we found two areas in pBMH06 and pBMH07 with the potential to form a perfect duplex of 46 and 49 nt, respectively, with parts of edited B. saltans ND5 mRNA, if G:U basepairing is allowed (Fig+ 1B)+ Primer extension analysis with total B. saltans RNA and oligonucleotides complementary to the 39 part of the encoded (putative) gRNAs, further showed the existence of RNAs with 59 ends at the positions expected (Fig+ 1B)+ From this, we concluded that these two 1+4-kb DNAs each contain a gRNA gene, completing their identification as the B. saltans equivalent of minicircles+ The two ND5 gRNA genes were of opposite polarity and located in different regions that lack any obvious sequence identity to the corresponding regions of other B. saltans minicircles+ Sections of other minicircles that aligned with these two gRNA genes (Fig+ 1A) appeared to be the only two locations that harbor gRNA genes (see below) and they are referred to as gRNA gene cassettes I and II (see Fig+ 1A,C)+ Both cassettes are preceded by a conserved 35-nt sequence element (inverted repeat, see Fig+ 1A) and are flanked by stretches of 8-10 C residues, although the location of the C-stretch downstream of cassette I varied between minicircles+ A map describing the features of a typical B. saltans minicircle is presented in Figure 1C+ …”
Section: Cloning and Sequencing Of B Saltans Minicirclesmentioning
confidence: 99%
“…In this article, we have characterized the minicircle component of mt DNA of the free-living bodonid B. saltans+ There can be little doubt that the 1+4-kb molecules that we analyzed represent the B. saltans equivalent of minicircles, as they harbor two gRNA genes and possess other minicircle-like features, such as a conserved region that includes a (degenerate) CSB-3 sequence, and a bent helix DNA element (Fig+ 1; see Ntambi et al+, 1984;Ray, 1989;Shapiro & Englund, 1995;Simpson, 1997)+ The identification of the gRNA gene cassettes proved to be a multi-step process+ First, we noted the potential of two almost diametrically opposed sequences on two different 1+4-kb DNA circles to form long duplexes (46 nt and 49 nt, respectively, including G:U pairs) with sections of edited ND5 mRNA from B. saltans (Fig+ 1)+ In the next phase of this work, we showed that these sequences were indeed each transcribed into an RNA with a 59 end at the expected position and we demonstrated that 14 45-70 nt, U-tail-possessing (putative) gRNAs were encoded at either one of these positions on different circles (Fig+ 2)+ The conserved region comprised a relatively large section of the B. saltans minicircles (nt 800-1140, see Fig+ 1A), substantially larger than the conserved part of minicircles from most trypanosomatid species+ Outside the fully conserved (.95%) region, there were other sections that are also relatively well conserved (see Fig+ 1), leading to an overall conservation of 63-74%+ In fact, the two gRNA gene cassettes that we have found resided in the only two sections that showed completely variable sequences+ Together with the experimental evidence that localized the 16 identified gRNA genes to either one of the gRNA gene cassettes (Figs+ 1 and 2), this strongly argues against the possibility of additional gRNA gene cassettes in B. saltans minicircles+ Nevertheless, the present data do not completely rule out the existence of minor minicirclesequence classes with different gRNA gene contents (Riley et al+, 1994)+ Interestingly, both gRNA gene cassettes proved to be flanked by C-rich sequences and preceded by a 35-nt conserved element, which (due to the opposite polarity of the two cassettes) manifested itself as an inverted repeat in the minicircle sequences of Figure 1A+ The role of these elements remains to be established, but their position and orientation relative to the gRNA genes suggests that they are involved in gRNA transcription or processing+…”
Section: Identification and Characterization Of B Saltans Minicirclementioning
confidence: 99%
See 1 more Smart Citation
“…Two large libraries were prepared from LEM125 kinetoplast DNA digested with enzymes that each cut almost all minicircles in the network at least once, Sau 3AI and MspI+ Several smaller libraries were also generated using ClaI, XbaI, EcoRI, SphI, and HindIII digestions+ Colonies were enriched for new minicircle classes by removing previously identified minicircle sequence classes+ Plasmids were isolated and the minicircle inserts completely sequenced+ The polarities of the minicircle sequences were determined by identification of the conserved CSB-1, -2, and -3 and the bend sequences (Ray, 1989)+ Guide RNA genes were identified by alignment of the portion of the variable region of the minicircles expected to contain the gRNA to all edited mRNA sequences )+ Twenty new gRNAs that mediate editing of the ND8, ND9, G4, and G5 mRNAs were discovered by this search (Figs+ 1-4)+ The cascades of overlapping gRNAs for the edited ND8, ND9, G4, and G5 mRNAs are almost complete+ There is, however, a gRNA missing for block VIII in ND8 G. Gao et al…”
Section: Identification Of New Minicircle-encoded Guide Rnas From Thementioning
confidence: 99%
“…The mitochondrial genome of trypanosomatid protozoa is composed of a single giant network containing two forms of catenated circular DNA molecules, maxicircles and minicircles (Simpson, 1987)+ The minicircles are present in approximately 10,000 molecules per network and the maxicircles in approximately 20-50 copies per network+ The maxicircle contains two rRNA genes and 18 structural genes+ Transcripts of 12 of the 18 genes of the maxicircle contain variable numbers of frameshifts that must be corrected for translation to occur (Horváth et al+, 2000)+ The transcripts are edited by the insertion and occasional deletion of U residues at specific sites within the gene, thereby creating open reading frames (Estévez & Simpson, 1999)+ The information for editing is contained in a class of small usually trans-acting RNAs known as guide RNAs (gRNAs), which are encoded both in the maxicircle and minicircle components of the mitochondrial DNA Sturm & Simpson, 1991)+ The gRNAs consist of a 59 anchor region that forms a duplex with the pre-edited mRNA just downstream of the first editing site, a central guiding region that contains guiding A and G nucleotides that can base pair with the inserted Us, and a posttranscriptionally added oligo[U] tail ranging from 5-30 nt in length of uncertain function )+ The mechanism of editing involves hybrid-ization of a specific gRNA forming the anchor duplex, endonuclease cleavage of the mRNA at the first mismatched base, addition of Us to the 39 end of the 59 cleavage fragment by a 39 terminal uridylyl transferase, base pairing of the added Us to the guiding nucleotides in the gRNA, and ligation of the two cleavage fragments Cruz-Reyes & Sollner-Webb, 1996;Kable et al+, 1996;Seiwert et al+, 1996)+ The editing machinery then moves upstream to the next editing site on the mRNA and the cycle is repeated+ Deletion editing involves removal of unpaired Us from the 59 cleavage fragment by a U-specific 39-59 exonuclease (Aphasizhev & Simpson, 2001) prior to ligation+ A single gRNA mediates the editing of a specific single block of editing sites in an mRNA+ In some cases, editing creates anchor sequences for hybridization of other overlapping gRNAs for editing of adjacent upstream blocks, thereby determining the observed overall 39 to 59 polarity of editing (Maslov & Simpson, 1992)+ A DEAD box protein with possible RNA helicase activity (Missel et al+, 1997) and a putative RNA ligase (McManus et al+, 2001;Rusché et al+, 2001;Schnaufer et al+, 2001) are the only components of the editing machinery established by gene knockout analysis+ In Leishmania tarentolae, the minicircle is approximately 900 bp in size and consists of a conserved region and a variable region+ The entire conserved regions are conserved in different minicircles within a trypanosomatid species and short segments within these regions are conserved between species and between genera+ The three short conserved sequences (CSB-1, -2, and -3; Ray, 1989) fo...…”
Section: Introductionmentioning
confidence: 99%